Praktik Khataman Digital Bagi Keluarga Bani Kh. Abdul Qodir Via Whatsapp Di Pondok Pesantren Mambaul Ulum Karang Anom, Lesong Daya, Batumarmar, Pamekasan - Moh. Samsul Ma’arif; Fadhoilul Khoir; Muhammad Fawaid Jufri; Ahid Dhiyaul Hikam; Ahmad Zaini (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study examines the practice of digital Qur’anic khataman conducted by the family of Bani KH. Abdul Qodir through a WhatsApp group at Pondok Pesantren Mambaul Ulum Karang Anom, Lesong Daya, Batumarmar, Pamekasan. The research aims to describe the implementation process of digital khataman and analyze its spiritual and social significance. This study employs a qualitative field research method with a descriptive approach within the framework of Living Qur’an studies. Data were collected through interviews, observation, and documentation, then analyzed using the interactive model of Miles and Huberman. The findings reveal that digital khataman is implemented through the distribution of juz among participants, individual Qur’anic recitation, reporting of completed recitations via WhatsApp, and the recitation of khatmil Qur’an prayers after all portions have been completed. Despite several obstacles, such as delayed completion of recitations, the activity continues through a system of reminders and coordination by group administrators. The practice is understood as a means of preserving family religious traditions and strengthening attachment to the Qur’an. Spiritually, it encourages regular recitation, increases religious awareness, and fosters inner peace. Socially, it strengthens family solidarity, maintains kinship ties, and reinforces collective identity. Therefore, digital khataman represents a contemporary form of Living Qur’an that demonstrates the adaptation of Islamic religious traditions to digital technology. Keywords: Living Qur’an; Digital Khataman; WhatsApp; Family Tradition; Religious Practice.